2022
DOI: 10.1002/jpen.2429
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum supplementation alleviates liver and intestinal injury in parenteral nutrition‐fed piglets

Abstract: Objective: Long-term parenteral nutrition (PN) causes PN-associated liver disease, for which therapeutic approaches are limited. This study aimed to investigate the effects of Lactobacillus plantarum CGMCC 1258 (LP) on liver and intestinal injury in PN-fed neonatal piglets. Methods:The piglets received PN with or without oral LP for 14 days. The levels of liver enzymes and inflammatory markers were measured using biochemical kits and quantitative real-time polymerase chain reaction. Serum fibroblast growth fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In this study, we found that all the indicated SCFAs decreased significantly in the TPN group. These findings were rational because one of our previous works has demonstrated that the abundance of SCFA-producing Lactobacillus decreased dramatically in the ileal content of TPN piglets [27]. In children, studies using fecal samples have also demonstrated that the abundance of SCFAs (butanoic and pentanoic acids) in SBS patients weaning on PN was significantly lower than their counterparts weaning of PN [28,29], concomitant with reduced abundance of SCFA-producing bacteria such as Lachnospiraceae and Ruminococcaceae.…”
Section: Discussionmentioning
confidence: 74%
“…In this study, we found that all the indicated SCFAs decreased significantly in the TPN group. These findings were rational because one of our previous works has demonstrated that the abundance of SCFA-producing Lactobacillus decreased dramatically in the ileal content of TPN piglets [27]. In children, studies using fecal samples have also demonstrated that the abundance of SCFAs (butanoic and pentanoic acids) in SBS patients weaning on PN was significantly lower than their counterparts weaning of PN [28,29], concomitant with reduced abundance of SCFA-producing bacteria such as Lachnospiraceae and Ruminococcaceae.…”
Section: Discussionmentioning
confidence: 74%